Gerakan Peduli Kesehatan Gigi dan Mulut: Edukasi Kesehatan Gigi dan Mulut untuk Anak Prasekolah TK Istiqbal Ngagel Rejo - Isnanto, Isnanto; Yulyana Sendia Martina; Hayatunnufus, Hayatunnufus; Laily, Rohisotul; Dwi Septiarini (EDUPEDIA Publisher, 2025)
Dental caries is a condition that can be experienced by anyone and can appear on one or more tooth surfaces. If left untreated, caries can develop deeper, from the enamel to the dentin, and reach the pulp. This disease is one of the most common dental health problems in children and is a major cause of tooth loss at an early age. The high incidence of dental caries in children is influenced by various factors, including bad habits in maintaining dental hygiene and unhealthy eating patterns. The importance of maintaining dental and oral health must be introduced from an early age so that children understand how to maintain dental hygiene properly. Educational activities regarding dental and oral health maintenance aim to increase awareness and knowledge of preschool children, such as those carried out in the program at Istiqbal Ngagel Rejo Kindergarten. The activity method used was counseling (lectures, questions and answers, and demonstrations of brushing teeth) using phantom teeth, toothbrushes, and flip charts. The results of the activity were an increase in the knowledge of preschool children at Istiqbal Kindergarten from the less to sufficient category. However, it did not reach the planned target, namely that the majority received the good category.